Collaborative Research with Parents and Local Communities: Organizing Against Racism and Education Privatization - Pauline Lipman (University of Lower Silesia, 2013)
The author discusses her collaborative research with parents and communities against neoliberal education policies in Chicago. The paper summarizes several projects that challenge racism and educational privatization: using social science data to challenge public school closings, collaboration with a community organization to tell the story of the effects of school closings and disinvestment on African American students and schools from their own perspective, and research for a city-wide coalition for an elected school governance board. The author uses these projects to illustrate multiple forms of activist scholarship and some of their complexities and contradictions.